2017
DOI: 10.1002/aic.16022
|View full text |Cite
|
Sign up to set email alerts
|

Studies on mild catalytic synthesis of methyl acrylate via one‐step aldol reaction

Abstract: One‐step catalytic synthesis of methyl acrylate from methyl acetate and trioxane, with 90.7% yield and 91.8% selectivity, was realized at 10–25°5. NMR analysis confirmed the ester enolization with generation of [i‐Pr2EtN‐H]+[TfO]− in the presence of i‐Pr2EtN and Bu2BOTf, which was affected by solvent and base. The depolymerization of trioxane into formaldehyde was catalyzed by Bu2BOTf. The in‐situ catalytic mechanism and efficiency of [i‐Pr2EtN‐H]+[TfO]− was determined and analyzed. Mechanism‐based kinetic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…Li et al compared the catalytic activity of different secondary amines and found that diethylamine obtains the highest yield of MAL (∼94%) 11 . Ionic liquid (IL) has been used in MAL preparation because of its excellent performance 12,13 and wide application 14‐16 . Wang et al reported a [Mim]Ac proton IL to synthesize MAL through the Mannich reaction 17 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al compared the catalytic activity of different secondary amines and found that diethylamine obtains the highest yield of MAL (∼94%) 11 . Ionic liquid (IL) has been used in MAL preparation because of its excellent performance 12,13 and wide application 14‐16 . Wang et al reported a [Mim]Ac proton IL to synthesize MAL through the Mannich reaction 17 .…”
Section: Introductionmentioning
confidence: 99%
“…11 Ionic liquid (IL) has been used in MAL preparation because of its excellent performance 12,13 and wide application. [14][15][16] Wang et al reported a [Mim]Ac proton IL to synthesize MAL through the Mannich reaction. 17 The ratio of raw materials, the amount of [Mim]Ac, and reaction conditions were systematically optimized, resulting in a 95.3% yield of MAL.…”
mentioning
confidence: 99%
“…Compared with [Omim]Cl/0.5ZnCl 2 , [Omim]Cl/2ZnCl 2 , and [Omim]Cl/3ZnCl 2 ionic liquids, the [Omim]Cl/4ZnCl 2 has higher content of [Zn 2 Cl 5 ] − species, which shows stronger Lewis acidity than [ZnCl 3 ] − according to the pyridine IR characterization results. As reported in the literatures, the decomposition of trioxane to formaldehyde units can proceed on strong Lewis acid sites, 61–67 which show equivalent activity to Brønsted acid sites, while both weak and strong Lewis acid sites exhibit good performance on insertion of formaldehyde monomer into the backbone of OMEs 51,53 . Therefore, the [Omim]Cl/ZnCl 2 ionic liquid with lower content of [Zn 2 Cl 5 ] − species, namely lower ratio between ZnCl 2 and [Omim]Cl, will be more advantageous for trioxane retention and thus result in slower transformative rate.…”
Section: Resultsmentioning
confidence: 90%
“…The use of Tx instead of FA, the latter generally available in aqueous solutions, is believed to increase the yield of MeGVL as the presence of water inhibits the α‐methylation reaction. The decomposition of Tx in the temperature range 483–503 K leads to the formation of three molecules of FA, which are essential for initiating the desired transformation . The comparative impact of the porous, acidic, and basic properties of the zeolites upon Cs loading on the yield of MeGVL was quantified, providing insights into the enhanced selectivity observed over the hierarchical zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…tion. [22][23][24] The comparative impact of the porous, acidic, and basic properties of the zeolitesu pon Cs loading on the yield of MeGVL was quantified, providing insights into the enhanced selectivity observed over the hierarchical zeolites. The synthesized MeGVL over the best-performing materialw as subjected to visible-light-induced polymerization to produce poly-(MeGVL)u sing graphitic carbon nitride (g-CN) as catalyst.…”
Section: Introductionmentioning
confidence: 99%